2004
DOI: 10.1186/1465-9921-5-1
|View full text |Cite
|
Sign up to set email alerts
|

TLR4 signaling is essential for survival in acute lung injury induced by virulent Pseudomonas aeruginosa secreting type III secretory toxins

Abstract: Background: The relative contributions of the cytotoxic phenotype of P. aeruginosa expressing type III secretory toxins and an immunocompromised condition lacking normal Toll-like receptor 4 (TLR4) signaling in the pathogenesis of acute lung injury and sepsis were evaluated in a mouse model for Pseudomonas aeruginosa pneumonia. By using lipopolysaccharide-resistant C3H/HeJ mice missing normal TLR4 signaling due to a mutation on the tlr4 gene, we evaluated how TLR4 signaling modulates the pneumonia caused by cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
62
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(65 citation statements)
references
References 38 publications
2
62
1
Order By: Relevance
“…In vitro, bone marrow cells lacking TLR4 exhibited blunted TNF-␣ expression when stimulated with P. aeruginosa. In vivo, the cytokine and inflammatory responses to pulmonary infection with P. aeruginosa were significantly impaired in TLR4 Ϫ/Ϫ mice compared with wild-type controls, consistent with recent observations in mice with nonfunctional mutations in TLR4 (14,44). Ramphal et al (46) similarly found reduced cytokine responses in TLR4…”
Section: Discussionsupporting
confidence: 76%
“…In vitro, bone marrow cells lacking TLR4 exhibited blunted TNF-␣ expression when stimulated with P. aeruginosa. In vivo, the cytokine and inflammatory responses to pulmonary infection with P. aeruginosa were significantly impaired in TLR4 Ϫ/Ϫ mice compared with wild-type controls, consistent with recent observations in mice with nonfunctional mutations in TLR4 (14,44). Ramphal et al (46) similarly found reduced cytokine responses in TLR4…”
Section: Discussionsupporting
confidence: 76%
“…Morphologic changes in the C3H/HeJ mice were not demonstrable during the first week of life, and the subsequent changes were coincident with bacterial colonization and inflammation. Although TLR4 signaling is essential for clearance of GNB in experimental models of pneumonia in adult mice (18,19,24), the present study demonstrates a potential role for TLR4 in preventing bacterial colonization in the developing lung of the C3H strain. In the cage system of our vivarium, immature mice are exposed to various bacteria in the litter and their excreta, but the absence of TLR4 signaling results in a significantly greater transient bacterial colonization of lungs in the C3H/HeJ strain compared with controls.…”
Section: Discussionmentioning
confidence: 97%
“…Toll-like receptor 4 (TLR4) serves as a PRR for GNB by recognizing lipopolysaccharide (LPS) (16) and mediating LPS responsiveness (17). Studies in adult mice lacking TLR4 signaling have shown that this receptor is essential for clearance of GNB (18,19). C3H/HeJ mice have a naturally occurring missense mutation in the cytoplasmic domain of TLR4 abolishing responsiveness to LPS (17).…”
mentioning
confidence: 99%
“…Inflammation, tissue damage, and lethality are diminished in the absence of TLR4 signaling (29). However, in the setting of infection with live bacteria, the contribution of TLR4 varies depending on the experimental model and type of organism used in the study (13)(14)(15)(30)(31)(32)(33)(34)(35)(36)(37). Most early studies used mouse strains with mutant forms of TLR4.…”
Section: Discussionmentioning
confidence: 99%